Pitchfork and Hopf bifurcations in an extended Lorenz system - Granada Díaz, Héctor Andrés; Olivar Robayo, Luis Eduardo; Casanova Trujillo, Simeón (Universidad Pedagógica y Tecnológica de Colombia, 2023)
An analytical classification in a three-dimensional parameter space is presented to describe the dynamics for an extended Lorenz system of the Li-Ou type, conditions are given to find supercritical and degenerate Hopf bifurcations and a pitchfork bifurcation. Finally, the theoretical results are compared with numerical simulations and bifurcation diagrams.